A brief report on the development of dorsal air sacs in hand reared Von der Decken's hornbills (Tockus deckeni). Issue 4 (November 2020) - Rusli, Mark
Several species of hornbills are known to develop dorsal air sacs after hatching, which present as a pocket of air under their skin. These increase in size as the chicks grow, and gradually disappear as the chicks develop feathers. However, this feature is not well-described, nor do we know the extent it occurs in Bucerotids. Here, it is reported in a clutch of hand-reared Von der Decken's hornbills ( Tockus deckeni ) ( n = 5) at Jurong Bird Park, Singapore. Air sacs were not present at hatch, but developed within 24 h, increasing in size until about 10 days of age. They gradually recede from this age and are not always inflated, disappearing at about 16 days of age when the chick has considerable feather growth. The functions of this unique feature are largely unclear, but it is thought to be mostly related to thermoregulation. Further research is required to determine this, possibly using captive specimens from zoological institutions as it is more difficult to collect data from wild birds.